Selective and Sustained Inhibition of Surface-bound Thrombin Activity by Intimatan/Heparin Cofactor II and Its Relevance to Assessing Systemic Anticoagulation In Vivo, Ex Vivo and In Vitro - Buchanan, Michael R.; Maclean, Glenn A.; Brister, Stephanie J. (Thrombosis and Haemostasis, 2001)
We compare the relative activities of surface-bound and fluid-phase thrombin and their inhibition by heparin and Intimatan, a novel heparin cofactor II (HCII) agonist. In vitro, we compared the observed amidolytic activities of fluid-phase and surface-bound thrombin with the expected activities based upon 125I-specific activity. In vivo, we compared the inhibitory effects of heparin and Intimatan on thrombin activity bound to injured vessel walls. In vitro, the correlations between observed and expected activities of fluid-phase and surface-bound thrombin, were: r = 0.9974, p < 0.001; and r = 0.9678, p < 0.001; respectively. In vivo, injured vessel wall surface-bound thrombin activity persisted for > 24 h. This activity was not inhibited by heparin, but was inhibited by Intimatan, p < 0.001.We conclude that surface-bound thrombin is as active as fluid-phase thrombin and remains protected from inhibition by heparin, thereby contributing to vessel wall thrombogenicity following injury. In contrast, surface-bound thrombin is inhibited by Intimatan, thereby effectively decreasing vessel wall thrombogenicity following injury in vivo.
Keywords: Surface-bound thrombin; heparin; Intimatan